The Ford Foundation And Development Of Western Education In Nigeria: A Historical Evaluation - Oladele, Adeoti Ezekiel (European Scientific Journal, ESJ, 2016)
The Post World War II years witnessed increasing involvement of international Non-Governmental Organizations (NGOs) in the social and economic transfiguration of the Third World nations. Nigeria as a developing economy did attract the attention of the Ford Foundation to the development of her social sector particularly. The paper examined the Ford Foundation engagements in all facets of the Nigerian educational system, namely, primary, secondary and tertiary levels. The resultant findings revealed that despite its constraints, the huge investments of the Ford Foundation in the areas of comprehensive high school education, teaching and research as well as information and communication technology, no doubt, helped in identifying and nurturing the potentials of Nigerian students for academic, technical or general education. The paper concluded that the involvement of the Ford Foundation in Nigerian educational development helped, in no small way, in re-directing the course of Nigeria’s educational system. It recommended that Nigeria government should redouble its efforts towards providing an enabling environment that will attract more credible NGOs like Ford Foundation and encourage them to play effective role not only within the educational sector but also in other key sectors such as agriculture, health, science and technology to assist the country achieve the much touted Millennium Development Goals.